The role of viruses in idiopathic peripheral facial palsy and cellular immune response - Kaygusuz, I; Gödekmerdan, A; Keles, E; Karlidag, T; Yalçin, S; Yidiz, M; Tazegül, A (W B Saunders Co-Elsevier Inc, 2004)
Purpose: The purpose of this study is to investigate the role of viruses on the idiopathic peripheral facial palsy and show the interaction of immune system. Materials and Methods: The levels of immunoglobulin (Ig) G and IgM antibodies against to varicella-zoster virus (VZV), herpes simplex virus (HSV), cytomegalovirus (CMV), Ebstein-Barr virus (EBV), and mumps virus in venous blood taken from patients in the amount of 10 mL have been investigated by enzyme-linked immunosorbent assay method. Tumor necrosis factor-alpha (TNF-alpha), interferon-gamma (IFN-gamma), and transforming growth factor-beta (TGF-beta) were also examined. Of lymphocyte subpopulation, antibodies of CD3(+), CD4(+), CD8(+), CD19(+), and CD16(+) plus 56(+) were analyzed. Results: Ten of the patients had HSV-1 IgG; 1 of the patients IgM, 5 of the patients EBV IgG, 6 of the patients VZV IgG, 1 of the patients IgM, 9 of the patients mumps IgG, 1 of the patients IgM, and finally in 7 of the patients CMV IgG antibodies were obtained. It was found that CD4(+) cell and ratio of CD4(+)/CD8(+) lower and the percentage of the CD8(+) and CD16(+) plus 56(+) cells higher compared with the control group (P <.05). The levels of TNF-alpha were lower, whereas IFN-gamma and TGF-beta1 were higher. Conclusion: It may be concluded from these results that VZV, HSV-1, CMV, EBV, and mumps virus play a significant role in the etiology of idiopathic peripheral facial palsy and activate the cellular immunity. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: Herpes-Simplex-Virus; Nerve Palsy; Paralysis; Infection; Acyclovir; Diagnosis; Type-1; Demyelination; Pathogenesis; Diseases